Tantangan Infrastruktur dan Biaya Pendidikan: Mengembangkan Model Pembelajaran yang Inklusif - Hadi Ardiansyah; Masduki Asbari; Ririn Maharani; Satria Yanuaril Akram (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
Over the past two decades, there has been a significant shift in higher education, especially in terms of teaching methods that must adapt to the learning styles of Generation Z students. The experience of a lecturer with more than 20 years of teaching reveals the challenges and transformations experienced, especially since the pandemic. Traditional teaching styles are no longer relevant to meet the needs of Generation Z who are accustomed to technology and gamification. This article uses a descriptive qualitative research method with a listening-noting technique to observe and record the development of digital interaction-based learning and the concept of gamification in higher education. The results of this study indicate the importance of adopting technologies such as virtual reality and artificial intelligence in creating personalized and interactive learning. In addition, this article highlights the challenges of education in Indonesia, such as the increasing cost of education and the low gross enrollment rate (APK) in higher education. This article concludes with suggestions on the importance of collaboration between educators, technology, and industry to create more inclusive and affordable education, and how the concept of a digital university can be a solution in the future.